Penas privativas de dignidade? A função da pena pela teoria dos sistemas autopoiéticos - Sampaio, André Rocha (2009)
The Federal Constitution of 1988 has brought deep changes in the Brazilian juridical system, among them, we can emphasize the appearance of the value dignity of the human person as a fundament of the Democratic State of Law. Taking in account that almost the entire juridical rules of penal execution dates back of a moment before the promulgation of the new Constitution, it became important to analyze all the penitentiary system on the perspective of the human dignity. With the proposal of minimize ideological influences and use an analyses different from the Cartesian analyses, we used the approach of the autopoietic systems theory of Niklas Luhmann, having as a goal to demonstrate clearly the salient aspects that differs what the juridical system disposes from what is empirically noticed in the Brazilian penitentiary system.